Tracking clinic using mobile application, GPS and Google Maps (GetClinic). / Muhammad Syazwan Asman - Asman, Muhammad Syazwan (2013)
If we entered to a unfamiliar place it is difficult to and a destination without any guide. Moreover, if there is an emergency case finding clinic in hurry is hard to find. Thus this project has been proposed to solve that problem. In addition, mobile application is the technique, this project give a great impact to the user. This application is using java as the language and sqlite for the database language. This application is developed in Eclispe software. The objectives of this project are provides direction to destination from location. As the result both of the objective is fulfilled and the application can be run in various version of android and in different brand. Average time taken of the out is less than 6 second with standard internet connection speed. Since this project is only a prototype, the data is limited and only covered partial of many clinics that available in Seri Iskandar. In future, this application need to widen up the area it covers increasing performs of the application in term of speed and interface. Hopefully this project will give benefits to its user.